Evaluation of cinnamon essential oil microemulsion and its vapor phase for controlling postharvest gray mold of pears (Pyrus pyrifolia). (24th September 2013) - Wang, Yifei; Zhao, Ruipeng; Yu, Ling; Zhang, Yunbin; He, Yan; Yao, Jie
Abstract BACKGROUND Essential oil of cinnamon (CM) is a potential alternative to chemical fungicides. Thus this work aimed to investigate the possible effects of CM microemulsions on decay developments and qualitative properties of pears. RESULTS The decay incidence of samples treated with 500 µg L−1 microemulsion was significantly reduced by 18.7% in comparison to that of 500 µg L−1 non‐microemulsion after 4 days' storage at 20 °C. In the vapor phase, the CM microemulsion with the lowest concentration had the best control for decay incidence and lesion diameter. The interval between inoculations also influenced decay development. Pears treated with Botrytis cinerea and immediately followed by CM microemulsion showed the lowest decay incidence. Moreover, in the natural decay experiment, the percentage of rotted pears was 3.8% in the CM microemulsion treatment and 5.8% in the control. CM microemulsion delayed the loss of ascorbic acid, yet it had no significant influence on pear qualities such as firmness and color. CONCLUSION CM microemulsion may be an alternative way to control the gray mold of pears without a negative influence on its qualities. © 2013 Society of Chemical Industry